Orthogonally Regulated Mechanical Strength and Molecular Delivery Capabilities Achieved in a Double Network Hydrogel Matrix. Issue 19 (20th May 2020) - Teng, Kaixuan; Luan, Xinglong; An, Qi; Zhao, Yantao; Hu, Xiantong; Zhang, Shuting; Zhuang, Jialin; Li, Xiaobo; Lu, Limei; Zhang, Yihe
Abstract: Specific mechanical properties and molecular delivery capacities are important parameters in biomedical materials. However, in most materials, these two properties are intertwined and orthogonal adjustments of each of these properties remains difficult. In this report we propose a hydrogel design strategy that permits orthogonal adjustment of the mechanical strength and molecular delivery properties. Our strategy involves employing a double‐network hydrogel whereby the PAM network is responsible for adjusting the mechanical strength, and a CD‐laden network tunes the molecular delivery speeds taking advantage of the affinity between the diffusive molecules and the matrix. The mechanical strengths between 50 and 350 Pa were varied in the hydrogel matrix, and molecular deliveries with times varying between 200 min and 133 h were achieved. A complex hydrogel matrix permits delivery of three molecules with dramatically different release profiles. Cell culturing results show the sensitivity of the cell's response to the tuning of mechanical strength and delivery efficiency. We believe that our hydrogel matrix design concept broadens the design scope and functions of biomedical materials. Abstract : We propose a new design concept of a double network hydrogel, allowing the separate adjustment of the mechanical strength and the molecular delivery properties. The molecular delivery properties of the hydrogel are tuned by molecularly specific, fast reversible bindings between the diffusive species and the hydrogel matrix. We expect the concept of the double network hydrogel to inspire functional designs using other material systems.